2022
DOI: 10.1002/anie.202203847
|View full text |Cite
|
Sign up to set email alerts
|

Directed Conformational Switching of a Zinc Finger Analogue Regulates the Mechanosensing and Differentiation of Stem Cells

Abstract: The dynamic conformational changes in the secondary structures of proteins are essential to their functions and can regulate diverse cellular events. Herein we report the design of a synthetic polymer-based secondary structure analogue of a zinc finger (ZnF) by introducing a zinc coordination motif to overcome the free energy barrier predicted by theoretical calculations and fold-free polymer chains. The conformational switching between unfolded and folded state of the ZnF analogue can be triggered in situ to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The process of mechanotransduction and differentiation of stem cells is highly dependent on the cell adhesion to the substrate. , Our previous study has demonstrated that the microstructure on the hPC surface enhanced the expression of total integrin α2, activation of integrin α3, and secretion of the ECM component Laminin-5 in hBMSCs, in comparison to sPC and mPC substrates . In this study, we further examined the focal adhesion complex, integrin β1 subunit activation, and FAK phosphorylation, all of which play a major role in promoting MSC osteogenic differentiation and osteoblast maturation. We observed that hBMSCs exhibited a greater number of focal adhesions on hPC substrate, as evidenced by vinculin staining (Figure A).…”
Section: Resultsmentioning
confidence: 98%
“…The process of mechanotransduction and differentiation of stem cells is highly dependent on the cell adhesion to the substrate. , Our previous study has demonstrated that the microstructure on the hPC surface enhanced the expression of total integrin α2, activation of integrin α3, and secretion of the ECM component Laminin-5 in hBMSCs, in comparison to sPC and mPC substrates . In this study, we further examined the focal adhesion complex, integrin β1 subunit activation, and FAK phosphorylation, all of which play a major role in promoting MSC osteogenic differentiation and osteoblast maturation. We observed that hBMSCs exhibited a greater number of focal adhesions on hPC substrate, as evidenced by vinculin staining (Figure A).…”
Section: Resultsmentioning
confidence: 98%